2019
DOI: 10.1177/1120672119854985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility of bacteria isolated in patients affected with blepharitis in a tertiary eye centre in Spain

Abstract: Purpose: To describe which bacteria can be found on lid margins in patients affected with blepharitis, to show their antibiotic susceptibility pattern, and to evaluate the antibiotic resistance trend of coagulase-negative Staphylococcus through time. Materials and methods: Consecutive cases of 198 eyes affected with blepharitis between 2012 and 2018 were reviewed. A sample was collected by rubbing a swab against the base of the eyelashes of both the eyes of all patients. The samples were inoculated in blood ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Bezza et al reported that the abundance of Propionibacterium acnes was almost the same in the blepharitis group and the normal control group ( 9 ). The differences between these studies were considered to be related to differences in environmental and culture conditions ( 6 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bezza et al reported that the abundance of Propionibacterium acnes was almost the same in the blepharitis group and the normal control group ( 9 ). The differences between these studies were considered to be related to differences in environmental and culture conditions ( 6 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, several studies have investigated the ocular surface microbiota of blepharitis using culture approaches and found that Staphylococcus epidermidis, Staphylococcus aureus, Corynebacterium macginleyi , and Propionibacterium acnes were the most common species that appeared in cultures of eyelid margin or conjunctival sac samples from either patients with blepharitis or healthy controls ( 7 10 ). The relative differences in the prevalence of each bacterium were remarkable among the study groups from different parts of the world, which was believed to be due to the effects of different climates and environments ( 6 , 11 , 12 ). However, it is still doubtful whether the results of culture, which is susceptible to the influence of culture conditions, can reflect the true composition of the microbiota.…”
Section: Introductionmentioning
confidence: 96%
“…The relative abundance (RA) of each member of the microbiome and interactions among microbial species are crucial for the homeostasis and sustainability of ecosystems (Wintermute and Silver, 2010;Kumar et al, 2016). Disruption of the stable state can lead to ocular surface diseases, such as dry eye, meibomian gland dysfunction (MGD), and blepharitis (Zhu et al, 2018;de Paula et al, 2019;Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These are assumed to be commensal bacteria, colonizing the mucosa and lid margins. Along with Staphylococcus aureus, CoNS are the most commonly isolated bacteria in patients affected by blefaritis, 14 keratitis, 15 and conjunctivitis. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…These are assumed to be commensal bacteria, colonizing the mucosa and lid margins. Along with Staphylococcus aureus, CoNS are the most commonly isolated bacteria in patients affected by blefaritis, 14 keratitis, 15 and conjunctivitis. 16,17 In our study, among the 183 isolates, predominant bacteria were Gram positive bacteria, in particular Staphylococcus species, out of which only 3,6% were Staphylococcus Aureus and 96,4% were CoNS, a percentage respectively much lower and much higher as compared to a report in northern Ethiopia.…”
Section: Discussionmentioning
confidence: 99%